ARTEFAK MANIK-MANIK DALAM PERSPEKTIF ARKEOLOGI (Beads Artifact on Archaeology Perspective) - Nasruddin, No First Name (BALAI ARKEOLOGI PAPUA, 2016)
Knowledge about objects beads ss cultural works, mainly because it is used for clothing and jewelry of the human body. Since when made and used, is a question that requires a search through research. Small objects is one of the many artifacts of human cultural objects can be studied through the field of archeology. Beads of all types, materials and co/ora, thought to have been present to accompany the man, from prehistoric times to the modem era. From archaeological research report states that the findings bead old age, among other things found in the cave sites such as Sulawesi, Mangkulirang East Kutai, Kalimantan and East Java and the surrounding environment Is in the karst region. This research aims to understand the early history of the presence of beads for human life is based on archaeological evidence that is already known. Through the identification of artifacts beads diversity, ranging from the type, shape up the material element, it can put forward a variety of beads found in Indonesia starting from stone material, glass, metal to organic materials. Beads that can be identified include stone beads, glass, and only a small amount of organic materials and metals. Beads, mainly dominated glass beads, particularly the type of monochrome and polychrome. In connection with the scientific effort, the methods and ways of working that are used to understand the data artifacts beads that am completely limited, by using the method; contextual analysis, analysis of typology, analogy, arid interpretation. AbstrakPengetahuan mengenai benda manik-manlk sebagai karya budaya, temtama karana digunakan untuk pakaian dan pertiiasan tubuh manusla. Sejak kapan dibuat dan dipakai, adalah suatu psrtanyaan yang meroerlukan penelusuran melalui penelitian. Benda kecil ini merupakan salah satu artefak dan sekian banyak benda budaya mantissa yang dapat dikaji melalui bidang artceoiogi. Manik-manlk dengan berbagaijenls, bahan dan wama, dlperkirakan telah hadir menemani manusia, sejak masa prasejarah hingga di jaman modern ini. Dari iaporan penelitian arkeologl menyebutkan bahwa temuan manik-manik yang berumur tua, antara lain ditemukan di situs-situs gua saperti Sulawesi, Mangkulirang, Kutal Timur, Kalimantan, dan di Jawa Timur dan sekitarnya yang berada di lingkungan kawasan karat. Penulisan Ini bertujuan untuk memahami sejanah awai kehadiran manik-manik bagi kehidupan manusia bendasarkan bukti-bukti arkeoiogi yang sudah diketahui. Melalui identifikasi keragaman artefak manik-manik, mulai dari sisl Jenis, bentuk hingga pada unsur bahan, maka dapat dikemukakan anaka ragam manik-manik yang ditemukan di Indonesia mulai dari bahan batu, kaca, logam hingga bahan organik. Manik-manik yang dapat di identifikasi meliputi manik-manik batu, kaca, dan hanya sedikit jumlahnya daribahan organik dan logam. Manik-manik itu, terutama dkJomlnasl manik-manik kaca, khususnya tips monokrom dan poiikrom. Sehubungan dengan upaya iimiah, maka metode dan cara keija yang digunakan untuk memahami data artefak manik-manik yang sifatnya serba terbatas itu, yaitu dengan menggunakan metode; anal Isis kontektual, analisis tipologi, analog!, dan penafeiran.